Ontogeny‐based immunogens for the induction of V2‐directed HIV broadly neutralizing antibodies. Issue 1 (January 2017) - Moore, Penny L.; Gorman, Jason; Doria‐Rose, Nicole A.; Morris, Lynn
Summary: The development of a preventative HIV vaccine able to elicit broadly neutralizing antibodies (bNAbs) remains a major challenge. Antibodies that recognize the V2 region at the apex of the HIV envelope trimer are among the most common bNAb specificities during chronic infection and many exhibit remarkable breadth and potency. Understanding the developmental pathway of these antibodies has provided insights into their precursors, and the viral strains that engage them, as well as defined how such antibodies mature to acquire breadth. V2‐apex bNAbs are derived from rare precursors with long anionic CDR H3s that are often deleted in the B cell repertoire. However, longitudinal studies suggest that once engaged, these precursors contain many of the structural elements required for neutralization, and can rapidly acquire breadth through moderate levels of somatic hypermutation in response to emerging viral variants. These commonalities in the precursors and mechanism of neutralization have enabled the identification of viral strains that show enhanced reactivity for V2 precursors from multiple donors, and may form the basis of germline targeting approaches. In parallel, new structural insights into the HIV trimer, the target of these quaternary antibodies, has created invaluable new opportunities for ontogeny‐based immunogens designed to select for rare V2‐bNAb precursors, and drive them toward breadth.